En busca de la memoria : el nacimiento de una nueva ciencia de la mente. (KATZ EDITORES, 2007)
The author relates how his own study of memory converged with four distinct disciplines to give rise to the development of a new science of the mind that has changed our understanding of learning, memory, and mental illness.